AN APPLICATION OF MIND MAPPING TEACHING MODEL TO ENHANCE NATURAL SCIENCE LEARNING ACHIEVEMENT IN THE FIFTH GRADERS IN THE FIRST SEMESTER AT SD N 4 KALIUNTU - Wibowo, Nur (Universitas Pendidikan Ganesha, 2017)
This study was aimed at enhancing natural science learning achievement in the fifth graders in the first semester at SD N4 Kaliuntu in the school year 2017/2018. The data for the studentsâ natural science learning achievement were collected with a test and assessment rubric. The data were analyzed using descriptive statistical analysis, quantitative descriptive method, and gain score (Gn). The result of data analysis showed an increaseÂ proven by the pretest score for the studentsâ science learning achievement of 65.7% , categorized as a low score. The science learning achievement score increased inÂ the first cycle to 71.63%, categorized as average which increased again in the second cycle to 82.34%, showing science learning achievement in the high category. So, there was an increase in learning achievement of 5.93 from pre-cycle to the first cycle, an increase in learning achievement of 10.71Â from the first cycle to the second cycle. Thus, it can be concluded that there was an increase in the studentsâ natural science learning achievement in this study through the implementation ofÂ Mind Mapping teaching model.